2015
DOI: 10.1186/s12879-016-1384-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of drug treatment outcome in clarithromycin-resistant Mycobacterium avium complex lung disease

Abstract: BackgroundAlthough the isolation of clarithromycin (CAM)-resistant Mycobacterium avium complex (MAC) indicates a poor treatment outcome and increased mortality, there have been only a few reports on drug treatment for CAM-resistant MAC lung disease. We aimed to reveal the effectiveness of the continuation of a macrolide and the use of a multidrug regimen in the treatment of CAM-resistant MAC lung disease.MethodsAmong patients with MAC pulmonary disease as defined by the 2007 criteria of the American Thoracic S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 26 publications
(40 reference statements)
1
40
1
1
Order By: Relevance
“…However, a recently published study from Japan found that macrolide monotherapy or a two-drug regimen that included a macrolide were previously administered in only 18% and 12%, respectively, of patients with macrolide-resistant MAC-LD (15). The majority (60%) of patients had received adequate long-term combination therapies prior to the emergence of macrolide resistance (15).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a recently published study from Japan found that macrolide monotherapy or a two-drug regimen that included a macrolide were previously administered in only 18% and 12%, respectively, of patients with macrolide-resistant MAC-LD (15). The majority (60%) of patients had received adequate long-term combination therapies prior to the emergence of macrolide resistance (15).…”
Section: Discussionmentioning
confidence: 99%
“…An AFBpositive sputum smear at the time of detection of macrolide resistance was more frequently observed in patients with unfavorable outcomes. During the management of patients with MAC-LD, preventing the emergence of macrolide resistance is critical, because the development of such resistance is strongly associated with treatment failure and increased mortality (14,15). The first study on macrolide-resistant MAC-LD from the United States was published in 2006 and found that the major reasons (76%) for the development of macrolide resistance were initial macrolide monotherapy and the combination of a macrolide and a fluoroquinolone (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…90 Treatment of patients with MAC pulmonary disease and macrolide resistance has low success rates with antibiotic therapy, and surgery is a possible treatment in these patients. 91,92 Two surgical studies using lobectomy and segmentectomy for isolated disease or disease not responding to several months of antibiotics showed that 92%-100% of patients underwent sputum conversion after surgery. 28,34 There was no operative mortality in these studies.…”
Section: Pathogenesismentioning
confidence: 99%